2021
DOI: 10.3390/ijms22041874
|View full text |Cite
|
Sign up to set email alerts
|

Arsenoplatin-Ferritin Nanocage: Structure and Cytotoxicity

Abstract: Arsenoplatin-1 (AP-1), the prototype of a novel class of metallodrugs containing a PtAs(OH)2 core, was encapsulated within the apoferritin (AFt) nanocage. UV-Vis absorption spectroscopy and inductively coupled plasma-atomic emission spectroscopy measurements confirmed metallodrug encapsulation and allowed us to determine the average amount of AP-1 trapped inside the cage. The X-ray structure of AP-1-encapsulated AFt was solved at 1.50 Å. Diffraction data revealed that an AP-1 fragment coordinates the side chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Recently, Ferraro and colleagues developed a novel FN loaded with Arsenoplatin-1 (Pt(µ-NHC(CH 3 )O) 2 ClAs(OH) 2 ), which combines the cytotoxic effects of both cisplatin and arsenic trioxide. Preliminary in vitro results showed that this novel formulation provides selectivity toward cancer cells, but, unfortunately, it was not tested in vivo [50].…”
Section: Fn-based Nps For Cancer Treatment In Preclinical Modelsmentioning
confidence: 99%
“…Recently, Ferraro and colleagues developed a novel FN loaded with Arsenoplatin-1 (Pt(µ-NHC(CH 3 )O) 2 ClAs(OH) 2 ), which combines the cytotoxic effects of both cisplatin and arsenic trioxide. Preliminary in vitro results showed that this novel formulation provides selectivity toward cancer cells, but, unfortunately, it was not tested in vivo [50].…”
Section: Fn-based Nps For Cancer Treatment In Preclinical Modelsmentioning
confidence: 99%
“…Recently, encouraging attempts have been made to hamper the selectivity of AP-1 for cancer cells. One promising strategy involves horse spleen apo-ferritin nanocages, which can be used to encapsulate arsenoplatins, leading to an effective improvement of the selectivity for the A431 (human epidermoid carcinoma) and SVT2 (murine BALB/c-3T3 fibroblasts transformed with SV40 virus) cancer cells with respect to HaCaT (immortalized human keratinocytes) and Balb/c-3T3 (immortalized murine BALB/c-3T3 fibroblasts) healthy cells [ 121 ].…”
Section: The Strategiesmentioning
confidence: 99%
“…Another evidence of AP-1 targeting His residue was offered by a recent study, in which AP-1 was placed into the apoferritin (AFt) nanocage; the resulting X-ray structure revealed the coordination of the AP-1 fragment to the side chain of a His residue. 19 The present study has a twofold objective.…”
Section: Introductionmentioning
confidence: 99%